2011
DOI: 10.1177/1352458511431724
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Sclerosis Work Difficulties Questionnaire

Abstract: The MSWDQ is a valid and internally reliable measure of workplace difficulties in PwMS. Physical difficulties, as well as cognitive and psychological difficulties were important predictors of workplace outcomes and expectations about future employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 35 publications
0
49
0
1
Order By: Relevance
“…Finally, Honan et al (2012) published a validation study of the Multiple Sclerosis Work Difficulties Questionnaire. In this study, they enrolled 189 MS patients, of whom 54% were employed: the instrument indicated 34-40% of issues related to work reduction, cessation or change in work type.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Honan et al (2012) published a validation study of the Multiple Sclerosis Work Difficulties Questionnaire. In this study, they enrolled 189 MS patients, of whom 54% were employed: the instrument indicated 34-40% of issues related to work reduction, cessation or change in work type.…”
Section: Resultsmentioning
confidence: 99%
“…The MS Work Difficulties Questionnaire (MSWDQ) (Honan et al, 2012) is a 50-item test asking patients to rate from 0 (never) to 4 (almost always) the frequency of difficulties across several domains of functioning over the last four weeks. Data show that the scores generated from this test across all subscales are related to a reduction in hours worked since the diagnosis of MS. Glanz et al (2012) have reported on a subset of 285 employed MS patients participating in the CLIMB study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Unemployment rates for people with MS (PwMS) are estimated to be disproportionately high in comparison to both the general population, and to other groups of employees with severe and chronic disabilities. 4,5 While factors related to the ability of employees with MS to remain at work have been found to be mainly disease related, 6 these difficulties are compounded by a perceived lack of support from employers and co-workers.…”
Section: Introductionmentioning
confidence: 99%